HIGH-SENSITIVE GAS CHROMATOGRAPHIC-MASS SPECTROMETRIC DETERMINATION OF ESTERS OF O-PHTHALIC ACID IN WATER WITH LIQUID-PHASE MICROEXTRACTION - V. A. KRYLOV,; V. V. NESTEROVA, (International Journal of Pharma and Bio Sciences, 2016)
It has been shown that the ultrasound-assisted emulsification-microextraction is an efficient method for preconcentration of esters of Ð¾-phthalic acid. Application of extract capillary collection solved the problem of low-density (“light”) extractant sampling. The loss of the extractant during extraction due to evaporation and dissolution were measured and they were statistically insignificant. Rayleigh distillation method has been proposed for purification of the extractant. It has been found that leaching of o-phthalates into the carrier gas flow from chromatographic septum is the source of systematic errors in impurities determination. The relative expanded uncertainty of o-phthalates determination is at the level of 12–39 %. The limits of detection of esters of Ð¾-phthalic acid achieved are at the level of 4×10-6–1×10-5 mg L-1 and are highly competitive with the best world results.